Dobre Claudia Florentina, Ni victime ni héroïne. Les anciennes détenues politiques et les mémoires du communisme en Roumanie, Bucharest: Electra, May 2019, pp. 245. - Stamati, Iurie (Sensus Historiae, 2019)
This study provides a synthesis of Dr. Claudia Florentina Dobre’s contribution to research on the memory paradigm of the communist system in Romania, with a particular emphasis on the gender perspective. The analysis centers on the revised and updated edition of her doctoral thesis, in which the author deconstructs the memorial discourse of former female political prisoners.